Morphological, yield and protein profiling analysis among Schizophyllum commune natural strains, hybrids and hybrids of gamma-irradiated monokaryotic mycelia / Khairunnisa Abdul Rashid - Khairunnisa , Abdul Rashid (2019)
Cultivation of edible mushroom is rising due to their culinary, nutritional and medical value. The application of genetic diversity in mushroom breeding is crucial to search for new species and to enhance the existing species in terms of high yield and improved quality of fruiting bodies to meet the increasing demands from the society. The aims of this study are to evaluate sporophores of novel hybrids of Schizophyllum commune obtained by hybridisation and mutation and to profile proteome of hybrids by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). In this study, three native strains of S. commune were selected as the parental strains where two strains are from Malaysia (w1 and w2) and another from Thailand (R). Traditional cross-breeding (hybridisation) and induce mutation by gamma radiation were applied as the method for the development of new strains with novel characteristics. Thirteen hybrids were produced by hybridisation between monokaryotic w1 and w2, while two hybrids were generated by the hybridisation between w1 and R. Ten strains were developed by the method of gamma radiation. All fifteen new hybrids were evaluated based on several aspects, which includes mycelial growth rate, mycelial density, the width of sporophore, yield, biological efficiency, and protein profiling by SDS-PAGE. By using the protein profile, the electrophoretic protein pattern and similarity coefficient of each strain were compared with the parental strains. Hybrids showed various diversity at the morphological characteristics and protein profiling. The results obtained in this study proved that hybrid w1bw2f, w1dw2f, w1Lw2a, Ir-w1dRa, Ir-w1dw2d, Ir-w1ew2a, Ir-w1ew2d and Ir-w1gw2a exhibited high potential to be commercialised. Moreover, the biological efficiency of w1bw2f, w1dw2f, w1Lw2a, Ir-w1dRa, Ir-w1dw2d, Ir-w1ew2a, Ir-w1ew2d and Ir-w1gw2a were 34.74 ± 1.54 %, 27.38 ± 0.93 %, 33.84 ± 1.12 %, 29.07 ± 2.46 %, 29.14 ± 0.56 %, 28.72 ± 0.61 %, 28.67 ± 1.21 %, and 32.87 ± 0.91 % respectively. Most of the strains were able to be distinguished from one another except w1aw2a and w1bw2a. This enabled finger printing of the strains to protect breeder’s rights. The similarity calculated on the basis of the presence and absence of bands ranged from 14 % to 92 %. Hybridisation and gamma induction were able to enhance the characteristics of the strains and alter the protein profile of the hybrids. The good features of these hybrids may contribute to the variety in the mushroom industry and better commercialisation value.